The Management of Cooperative Learning Strategy in Improving Discipline Character at Cut Nya’ Dien Vocational High School Semarang - Anggraini, Yeni; Raharjo, Tri Joko; Mulyono, Sungkowo Edy (Educational Management, 2019)
Cooperative learning strategy is grouping students in class into a small group so that the students can cooperate with other students with the maximum abilities they have and learn from each other in the group.The aims of this research are to describe and analyze the planning, organization and evaluation of cooperative learning strategies in improving discipline character and building the morale of students in Cut Nya’ Dien Vocational High School Semarang. The method used in this research was qualitative approach. The subjects of this research were obtained from the principal, deputy head of curriculum sector curriculum, educators and students. Data collection techniques used in this research wereinterview, observation, and documentation. The location of this research was in Semarang City with the research objectives was Cut Nya’ Dien Vocational High School Semarang. The testing technique used for thevalidity of the data was peer examination, perseverance of observation, and triangulation. This research used the following steps as data analysis techniques used, they were data reduction, data presentation, and verification. The results of this research showed that: 1) The planning of the management of cooperative learning strategies in improving discipline character and building the morale of students in Cut Nya’ Dien Vocational High School SemarangSemarangstarting by creating vision, mission and goals of the school, cooperative learning strategies, determining facilities and schedules. 2) The Implementation was carried out with a system of distribution of schedules in the beginning of the new semester, for learning strategy using on of model of cooperative learning strategy that was jigsaw model and it was included in lesson plan. 3) The evaluation of the management of cooperative learning strategy in improving discipline character and building the moral of students in Cut Nya’ Dien Vocational High School SemarangSemarang through process evaluation and outcome evaluation.